The budding yeast GSK-3 homologue Mck1 is an essential component of the spindle position checkpoint - Maniyar, Siddhi; Polat, Irem; Pereira, Gislene (Open biology, 2022)
The spindle position checkpoint (SPOC) is a mitotic surveillance mechanism in Saccharomyces cerevisiae that prevents cells from completing mitosis in response to spindle misalignment, thereby contributing to genomic integrity. The kinase Kin4, one of the most downstream SPOC components, is essential to stop the mitotic exit network (MEN), a signalling pathway that promotes the exit from mitosis and cell division. Previous work, however, suggested that a Kin4-independent pathway contributes to SPOC, yet the underlying mechanisms remain elusive. Here, we established the glycogen-synthase-kinase-3 (GSK-3) homologue Mck1, as a novel component that works independently of Kin4 to engage SPOC. Our data indicate that both Kin4 and Mck1 work in parallel to counteract MEN activation by the Cdc14 early anaphase release (FEAR) network. We show that Mck1's function in SPOC is mediated by the pre-replication complex protein and mitotic cyclin-dependent kinase (M-Cdk) inhibitor, Cdc6, which is degraded in a Mck1-dependent manner prior to mitosis. Moderate overproduction of Cdc6 phenocopies MCK1 deletion and causes SPOC deficiency via its N-terminal, M-Cdk inhibitory domain. Our data uncover an unprecedented role of GSK-3 kinases in coordinating spindle orientation with cell cycle progression.